2003
DOI: 10.1080/01926230390201075
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Bioactivation and Toxicity of Dichlorophenyl Methylsulphone in Rat Olfactory Mucosa

Abstract: This study aimed to explain the isomer-and site-specific toxic effects of dichlorophenyl methylsulphone in the olfactory mucosa of rats. A single ip dose of the 2,6-chlorinated isomer (16 or 65 mg/kg) induced necrosis preferentially in the Bowman's glands and neuroepithelium in the dorsomedial part of the olfactory region. Only minor damage occurred at this site in rats dosed with the 2,5-chlorinated isomer (65 mg/kg). A strong concentrationand time-dependent covalent binding of the 14 C-labeled 2,6-isomer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Aryl methyl sulfones (Figure 4) are biotransformants formed from chloro aryl hydrocarbons derived from compounds such as 1,1,1-trichloro-2,2-bis( p -chlorophenyl)ethane (DDT) and polychlorinated biphenyls (PCBs) following conjugation with glutathione (GSH) and degradation via mercapturic acid derivatives. 2,6-dichlorophenyl methylsulfone, as a single ip dose, produced necrosis preferentially in the BG and neuroepithelium in the dorsomedial olfactory region (Franzén et al, 2003), probably mediated by CYP2A5 activation, one of the prominent CYPs in the mouse (Zhuo et al, 2004; Franzén et al, 2006). By contrast, only minor damage occurred at this site in rats dosed with the 2,5-chlorinated isomer.…”
Section: Rodent Nasal Cytotoxinsmentioning
confidence: 99%
“…Aryl methyl sulfones (Figure 4) are biotransformants formed from chloro aryl hydrocarbons derived from compounds such as 1,1,1-trichloro-2,2-bis( p -chlorophenyl)ethane (DDT) and polychlorinated biphenyls (PCBs) following conjugation with glutathione (GSH) and degradation via mercapturic acid derivatives. 2,6-dichlorophenyl methylsulfone, as a single ip dose, produced necrosis preferentially in the BG and neuroepithelium in the dorsomedial olfactory region (Franzén et al, 2003), probably mediated by CYP2A5 activation, one of the prominent CYPs in the mouse (Zhuo et al, 2004; Franzén et al, 2006). By contrast, only minor damage occurred at this site in rats dosed with the 2,5-chlorinated isomer.…”
Section: Rodent Nasal Cytotoxinsmentioning
confidence: 99%
“…We have recently reported that 2,6‐diClPh‐MeSO 2 is rapidly metabolised to a covalently bound metabolite in rat olfactory microsomes and Bowman's glands, while covalent binding of the 2,5‐chlorinated isomer is very low (Franzén et al 2003). Accordingly, the 2,6‐dichlorinated isomer caused necrosis in the Bowman's glands and degeneration of the olfactory epithelium 24 hr after dosing also in rats (Franzen et al 2003). As expected from the lack of covalent binding, the 2,5‐dichlorinated isomer did not cause any histological changes in the olfactory mucosa in rats.…”
mentioning
confidence: 99%